On belief functions and random sets - Hung T. Nguyen (2018)
We look back at how axiomatic belief functions were viewed as distributions of random sets, and address the problem of joint belief functions in terms of copulas. We outline the axiomatic development of belief functions in the setting of incidence algebras, and some aspects of decision-making with belief functions. © 2012 Springer-Verlag.